أثر ثقافة المؤسسة على إدارة التغيير وأداء العاملين في مؤسسات تربوية وعامة مختارة في سلطنة عمان : دراسة مقارنة - بوسعيدي، أحمد سعيد علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study aimed to achieve a set of objectives mainly focused on studying the impact of the institution's culture on managing change and the performance of employees in selected educational and public institutions in the Sultanate of Oman: A comparative study. The study dealt with four variables represented in the independent variable (the culture of the institution), the dependent variables (change management, employee performance), and the interactive variable (type of institution). To achieve the objectives of the research, the researcher used a random stratified sample of (313) employees by focusing on the opinion poll of middle administrative levels (Department Director - Department Assistant Director - Section Head) in governmental and private institutions in the Sultanate of Oman [Ministry of Education - Consumer Protection Authority - Oman Telecommunications Company (Omantel)] by using the quantitative approach (descriptive and predictive) by relying on the questionnaire as a method for collecting data and information through field visits to the study sample, and the researcher also used the qualitative approach by conducting a number of qualitative interviews, the researcher relied on structural equation modeling using the Smart PLS statistical program in analyzing the data. The researcher reached a set of conclusions, the most important of which is the existence of a positive, direct and statistically significant impact of the institution's culture in managing change and the performance of workers in government and private institutions in the Sultanate of Oman, There is also a positive, direct and statistically significant effect of managing the change in the performance of employees, and there is also a positive, direct and statistically significant effect of the interactive effect of the type of institution on the performance of employees. He concluded a set of recommendations, perhaps the most important of which is the interest in establishing an institutional culture based on oversight, teamwork, participation in decision-making, interest in managing change at the governmental and private levels, the agility of the organizational structure, the need to activate digital government, electronic transformation, and the preparation of high-level training programs in The leadership targets the management (senior, middle, and executive) in governmental and private institutions.